Optimal design of pipe diameter in water distribution system by multi-objective differential evolution algorithm: A case study of small town in Chiang Mai - Warisa Wisittipanich (2018)
© Springer Nature Singapore Pte Ltd. 2019. Water distribution system (WDS) plays a vital role in supplying water for population living in the city and urban areas. An expensive infrastructure of the WDS drives researchers to seek the least-cost design. This paper first presents the mathematical model to determine the optimal design for the WDS with two conflicting objectives; minimization of construction cost and minimization of total head loss in the network. To deal with large-scale problem in the real-world practice, metaheuristic approach is required to solve the problem. Therefore, this study proposes Differential Evolution (DE) algorithm with encoding and decoding procedures to handling the complexity of decision making in designing pipe sizes of all arcs in the water distribution network. The experiments are executed using the scenarios from the real case-study. Results obtained show that the proposed DE is able to find good a quality front with a set of non-dominated solutions in a single run without prejudice.